Snake Fungal Disease (Ophidiomycosis) in Northern Pine Snakes (Pituophis melanoleucus melanoleucus) in New Jersey: Variations by Year, Sex, and Morphological Sampling Site - Joanna Burger; Christian Jeitner; Robert T. Zappalorti; John Bunnell; Kelly Ng; Emile DeVito; David Schneider; Michael Gochfeld (Journal of Fungi)
Ophidiomyces ophidiicola, the fungus causing Snake Fungal Disease (SFD) or ophidiomycosis, is prevalent in North American snakes and can have deleterious population effects. Northern pine snakes (Pituophis melanoleucus melanoleucus) in New Jersey often test positive for ophidiomycosis. In this paper, we use qPCR to examine changes in prevalence from 2018 to 2023, and differences by age, sex, and morphological sampling locations. We swabbed ventral surfaces, head, and cloaca of snakes, and lesions and eyes if there were clinical ophidiomycosis signs. A snake was considered positive if any site was positive by qPCR. The prevalence was 47% (2018), increased to 100% (2022), but declined to 46% in 2023. The prevalence was highest in snakes with lesions (46–100%); head swabs had the lowest rates. The more lesions a snake had, the more likely it was that at least one would be positive. Males had significantly more lesions than females, but the prevalence was similar. In 2023, the prevalence of O. ophidiicola was low, but the prevalence of lesions did not decrease as markedly. We discuss the temporal changes in the positivity for O. ophidiicola and its implications for ophidiomycosis effects, suggesting that the fungus is endemic in this population.